Tanggung Gugat Risiko Majikan atas Perbuatan Melanggar Hukum Bawahannya dalam Kecelakaan Lalu Lintas oleh Truk Tronton di Balikpapan: Siapakah yang Bertanggung Gugat dan Bagaimana Bentuk Ganti Kerugiannya? - Krisna Angela (Jurnal Hukum Lex Generalis, 2022)
Recently, there was an accident caused by a tronton truck driver while doing his job. This accident in Balikpapan caused fatalities, injuries, and vehicle damage. Based on this, the author wants to examine the liability of the accident and the form of compensation for the victims. The result of the study indicates that the employer is liable for losses arising from unlawful acts committed by his employee while doing his job as regulated in Article 1367 (3) BW. In addition, victims of this accident can claim material and immaterial compensation which accordance with Article 1370 BW and Article 1371 BW.